2017
DOI: 10.5958/0974-8164.2017.00031.4
|View full text |Cite
|
Sign up to set email alerts
|

Weed management in irrigated dry-seeded rice

Abstract: A field experiment was conducted during Kharif 2015 and Summer 2016, at Agricultural Research Station, Dhadesugur, University of Agricultural Sciences, Raichur, Karnataka, India, to study the effect of different herbicides for control of weeds in irrigated dry-seeded rice. The dominant weeds in fields were Echinochloa sp. Panicum repens, Cynodon dactylon, Bracharia mutica, Digitarias anguinalis and Leptochloa chinensis among grasses, Eclipta alba,Commelina communis and Ludwigia parviflora as among broad-leaf w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…These results were conformity with the findings of Yadav et al (2007) which stated the effectiveness states that, Efficacy of penoxsulam in controlling weeds and increasing rice grain yield. Similar findings were also reported by Ramesha et al (2017), who recorded, post-emergence application of penoxsulam 10 g/l + bentazone 360 g/l SC (2500 ml/ ha) effective control weeds and to obtain higher grain yield in irrigated dry-seeded rice.…”
Section: Effect On Weed Control Efficiency (Wce) and Grain Yieldsupporting
confidence: 89%
“…These results were conformity with the findings of Yadav et al (2007) which stated the effectiveness states that, Efficacy of penoxsulam in controlling weeds and increasing rice grain yield. Similar findings were also reported by Ramesha et al (2017), who recorded, post-emergence application of penoxsulam 10 g/l + bentazone 360 g/l SC (2500 ml/ ha) effective control weeds and to obtain higher grain yield in irrigated dry-seeded rice.…”
Section: Effect On Weed Control Efficiency (Wce) and Grain Yieldsupporting
confidence: 89%
“…) as post-emergence at 2-4 leaf stage of weeds fb mechanical weeding at 50 DAS in semi dry rice. Nagarjun et al [64] at Main Research Station, Hebbal, Bengaluru revealed that with application of pendimethalin fb Trifamone and Ethoxysulfuron and pendimethalin (38.7% CS) fb penoxsulam + cyhalofop butyl the grain yield was found to be 4320 kg ha Hemalatha et al [65] revealed that preemergence application of pendimethalin fb postemergence application of metsulfuron methyl + chlorimuron ethyl registered the highest weed control efficiency (WCE) (89.7%) which was comparable with weed free check (90.6%). Ramesha et al [66] stated that pre-emergence application of pretilachlor + pyrazosulfuron-ethyl (600 + 15 g/ha) and twice hand weeded check (20 and 40 DAS) recorded significantly lower grassy and broad leaved weeds with higher WCE compared to bispyribac-sodium (25 g ha -1…”
Section: Effect Of Sequential Herbicides Application On Yield and Yie...mentioning
confidence: 99%